Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Inter- and intraspecific variability of total mercury concentrations in bats of Texas (USA) - Matthew C. Parker; Sarah R. Fritts; Sara P. Weaver; Melissa B. Meierhofer; Jessica Dutton (Environmental Research, 2024)

The effect of particle size on oral bioavailability and bioaccessibility of soil Ni from different sources - Luba Vasiluk; Jessica Sowa; Paul Sanborn; Michael D. Dutton; Beverley Hale (Environmental Pollution, 2023)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Mercury Concentrations in Whale Shark (Rhincodon typus) Embryo Muscle Tissue - Jessica Dutton; Jessica C. Hobbs; Shoou-Jeng Joung; Jennifer V. Schmidt (Bulletin of Environmental Contamination and Toxicology, 2023)

Relationship between trace element concentrations and body length in dolphinfish (Coryphaena hippurus) in the northwest Atlantic Ocean - Jessica Dutton (Environmental Science and Pollution Research, 2023)

An HSI-R1 Cross-Campus Partnership Model to Enhance Recruitment and Retention of Underrepresented Students in the Geosciences - Adriane Jones; Diane Kim; Beth Rabin; Jessica Dutton; Karla Heidelberg (Oceanography, 2023)
To help strengthen the United States’ capacity for scientific advancement, technological innovation, and climate solutions by building diversity in the geosciences, Mount Saint Mary's University (a Hispanic Serving Institution, women's college, and primarily undergraduate institution) partnered with the University of Southern California (a research-intensive university) to establish the Geopaths Catalina Scholars Program to introduce and expand geosciences opportunities for MSMU students.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Exploring the Use of SEM–EDS Analysis to Measure the Distribution of Major, Minor, and Trace Elements in Bottlenose Dolphin (Tursiops truncatus) Teeth - Meaghan A. McCormack; Wayne E. McFee; Heidi R. Whitehead; Sarah Piwetz; Jessica Dutton (Biological Trace Element Research, 2022)

Comparison of Maternal and Embryonic Trace Element Concentrations in Common Thresher Shark (Alopias vulpinus) Muscle Tissue - Jessica Dutton; Vittoria M. Venuti (Bulletin of Environmental Contamination and Toxicology, 2019)

Maternal transfer of trace elements in the Atlantic horseshoe crab (Limulus polyphemus) - Aaron K. Bakker; Jessica Dutton; Matthew Sclafani; Nicholas Santangelo (Ecotoxicology, 2017)

Spatial and temporal variation in distribution and protein ubiquitination for Mytilus congeners in the California hybrid zone - Jessica M. Dutton; Gretchen E. Hofmann (Marine Biology, 2008)